Optical coherence tomography for examining retina in patients with HIV/TB coinfection - E.A. Burylova; A.P. Demin; S.N. Skornyakov; E.V. Sabadash (РМЖ "Клиническая офтальмология")
E.A. Burylova, A.P. Demin, S.N. Skornyakov, E.V. Sabadash Ural Scientific Research Institute of Phtysiopulmonology – Branch of the National Medical Research Center of Phthisiopulmonology and Infectious Diseases, Ekaterinburg, Russian Federation Aim: to assess the retina (including peripapillary retinal nerve fiber layer/RNFL and retinal vessel diameter) in patients with tuberculosis (TB) or HIV/TB coinfection in the lack of abnormalities detected by standard eye exam using optical coherence tomography (OCT). Patients and Methods: all patients were divided into three groups. Group 1 (n=19) included patients with HIV/TB coinfection. Group 2 (n=18) included patients with pulmonary and extrapulmonary TB. Group 3 (n=20) included healthy volunteers (controls). All patients underwent standard eye exam and OCT (iVue-100 v3.2, Optovue, USA) to measure peripapillary RNFL thickness, central macular thickness, and the first-order retinal vessel diameter (eight vessels). Results: OCT demonstrated greater peripapillary RNFL thickness in the nasal sector (by 13.4–18.3%) and central macular thickness (by 4.0–7.5%), narrowing of retinal arteries, and enlargement of veins (predominantly temporal). These patterns may illustrate retinal microcirculation in the setting of a pathological condition (HIV/TB, including highly active antiretroviral therapy [HAART]) and be a harbinger of further abnormalities of ocular structures and central nervous system. Conclusion: OCT identifies changes in vessel diameter, central macular thickness, and peripapillary RFNL thickness before visual disturbances in preclinical eye changes in patients with HIV/TB coinfection. Keywords: HIV, tuberculosis, optical coherence tomography, calipermetry, retina. For citation: Burylova E.A., Demin A.P., Skornyakov S.N., Sabadash E.V. Optical coherence tomography for examining retina in patients with HIV/TB coinfection. Russian Journal of Clinical Ophthalmology. 2022;22(1):23–29 (in Russ.). DOI: 10.32364/2311-7729-2022-22-1-23-29.